Standpoint Suicide Attempts Dalam Film Kembang Api - Rahmansyah, Artaji; SM, Anis Endang; Dianthi, Martha Herinazwi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Suicide is a serious public health issue, with approximately 800,000 deaths each year according to the World Health Organization (WHO). In Indonesia, suicides are increasing, reaching 971 incidents by 2023. The movie "Kembang Api" raises the issue of mental health, suicide and emphasizes the importance of the value of life. This research aims to analyze the reasons behind the suicide attempt in the movie "Kembang Api" through the Standpoint perspective using Roland Barthes' semiotic analysis. The method used in this research includes analyzing the visual and verbal signs in the film to reveal the emotional and psychological burden experienced by the characters. The results show that these signs reflect heavy emotional and psychological burdens, reinforcing the representation of the characters' reasons for considering suicide. The film depicts the complexity of each character's emotions and struggles, emphasizing the importance of empathy, social support and understanding of mental health issues. Thus, the movie "Kembang Api" becomes a social mirror that invites viewers to understand and support individuals struggling with emotional and psychological problems.